Impact of programming on primary mathematics learning - Laurent, Manon; Crisci, Rosamaria; Bressoux, Pascal; Chaachoua, Hamid; Nurra, Cécile; de Vries, Erica; Tchounikine, Pierre (Learning and Instruction, 2022)
The aim of this study is to investigate whether a programming activity might serve as a learning vehicle for mathematics acquisition in grades four and five. For this purpose, the effects of a programming activity, an essential component of computational thinking, were evaluated on learning outcomes of three mathematical notions: Euclidean division (N = 1,880), additive decomposition (N = 1,763) and fractions (N = 644). Classes were randomly assigned to the programming (with Scratch) and control conditions. Multilevel analyses indicate negative effects (effect size range −0.16 to −0.21) of the programming condition for the three mathematical notions. A potential explanation of these results is the difficulties in the transfer of learning from programming to mathematics.
Keywords: Computational thinking; Learning transfer; Mathematics learning; Primary school; Programming activity; Randomized trial